An acoustic study of vocal expression in two genres of Yoruba oral poetry - Akinbo, Samuel K.; Samuel, Olanrewaju; Alaga, Iyabode B.; Akingbade, Olawale (Frontiers in Communication, 2022)
This pilot study proposes an acoustic study of the vocal expressions in Ìjálá and Ẹ̀sà, two genres of Yorùbá oral poetry. The results of the study show that cepstral peak prominence (CPP), Hammarberg index and Energy of voiced sound below 500hz distinguish comparisons of Ẹ̀sà, Ìjálá and speech but are not as reliable as F0 height and vibrato. By comparing the pitch trajectories of the speech tones and poetic tunes, we show that poetry determines tone-to-tune mapping but can accommodate language when it is feasible. The results of our investigation are not only in line with the previous impressionistic observations about vocal expression in Yorùbá oral poetry but contribute with new findings. Notably, our investigation supports vocal tremor as the historical origin of vibrato in Ìjálá. As a result of this, we strongly recommend the instruments of phonetic science for the study of vocal expression in African oral poetry.